2004
DOI: 10.1016/s1525-1578(10)60490-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Quantitative PCR of Microdissected Paraffin-Embedded Breast Carcinoma

Abstract: We studied the feasibility of using real-time quantitative PCR to determine HER-2 DNA amplification and mRNA expression in microdissected formalin-fixed, paraffin-embedded breast tumors and compared this with standard immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH) methods. Study cases (27 carcinomas and 3 ductal breast carcinoma in situ (DCIS) cases) showed varying Her-2 expression as determined by IHC (HercepTest). In carcinomas, there was a good correlation between HER-2 DNA amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
0
7

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 27 publications
(34 reference statements)
5
57
0
7
Order By: Relevance
“…Our data confirm previous studies demonstrating a substantial agreement between the results of HER2 status evaluation at the mRNA and protein levels (Ginestier et al, 2004;Gjerdrum et al, 2004;Vinatzer et al, 2005). A recent study that compared four different methods of assessment of HER2 status found a good correlation between RT -PCR and IHC, with an overall concordance that varied from 82 to 93% (Ginestier et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our data confirm previous studies demonstrating a substantial agreement between the results of HER2 status evaluation at the mRNA and protein levels (Ginestier et al, 2004;Gjerdrum et al, 2004;Vinatzer et al, 2005). A recent study that compared four different methods of assessment of HER2 status found a good correlation between RT -PCR and IHC, with an overall concordance that varied from 82 to 93% (Ginestier et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…However, routine methods of histological fixation and tissue processing could potentially damage or destroy RNA. In addition, dilution of tumour genomic material by nucleic acids from nonneoplastic tissue components is also a potential source of imprecision (Gjerdrum et al, 2004). Furthermore, the required equipment for kRT -PCR is not available in all histopathology laboratories and is quite expensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different authors state that a suitable DNA extraction method from FFPET is essential and needs to be chosen in relation to specific endpoints of a precise investigation; for instance, the increased length of amplicon or the increase of effective amplifiable copy number (Wang et al, 1996;Poljak et al, 2000;Gilbert et al,2007b). Therefore diverse nucleic acid extraction methods already described from FFPET, enable the use of DNA extracted for specific approaches: nested PCR-SSCP assay (Wang et al, 1996), RAPD-PCR (Jacobs et al, 2007), real-time quantitative PCR (Gjerdrum et al,2004), Southern blot hybridisation (e.g. Dubeau et al, 1986;Jackson et al, 1990;Rogers et al, 1990), flow cytometry (Leers et al,1999), microarray comparative genomic hybridization (Vékony et al, 2007) and SNP BeadArrays (Oosting et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the wide variety of methods for DNA extraction from FFPET, the majority was applied to collections of human samples, fixed with formalin (the fixative generally used in histopathological practice) (Gjerdrum et al, 2004). In veterinary clinics the procedures used are essentially the same.…”
Section: Introductionmentioning
confidence: 99%